Evaluation of appropriate indications for the use of sivelestat sodium in acute respiratory distress syndrome: a retrospective cohort study - Maki, Chika (Acute Med Surg, 2019)
AIM: Sivelestat sodium, a selective neutrophil elastase inhibitor, is the only commercially available, specific therapy for acute respiratory distress syndrome (ARDS); however, its clinical efficacy is controversial. We aimed to evaluate appropriate indications for its use in ARDS. METHODS: We studied 66 patients with ARDS who were treated with sivelestat sodium. They were divided into survivors (n = 37) or non‐survivors (n = 29) at 60 days, and clinical characteristics were analyzed. RESULTS: Patients’ backgrounds evaluated with the Acute Physiology and Chronic Health Evaluation II (APACHE II) score and the sequential organ failure assessment (SOFA) score were significantly different between both groups (survivors versus non‐survivors: APACHE II score, 14.7 ± 6.7 versus 20.5 ± 4.7, P < 0.01; SOFA, 7.25 ± 2.5 versus 9.82 ± 3.5, P < 0.01). There were no significant differences in other patients’ characteristics. On receiver operator characteristic analysis of APACHE II scores before the use of sivelestat sodium, the estimated cut‐off value for survival was calculated to be 18.5. On receiver operator characteristic analysis of the PaO(2)/FIO(2) ratio, the area under the curve was the highest 3 days after the treatment, with the optimal cut‐off point at 198. CONCLUSION: An APACHE II score ≤18, and a PaO(2)/FIO(2) ratio >198 at 3 days after the use of sivelestat sodium predicted a good outcome.